Synthesis of Cs2TeI6 thin film and its NO2 gas-sensing properties under blue-light illumination. (15th January 2022) - Hoat, Phung Dinh; Yun, Yeonghun; Park, ByungJin; Hung, Pham Tien; Hien, Vu Xuan; Lee, Joon-Hyung; Lee, Sangwook; Heo, Young-Woo
Abstract: In this study, a thin film of Cs2TeI6 perovskite with a thickness of 1.27 mm was prepared on a glass substrate via a non-solution process. The characteristics of the material such as phase structure, morphology, optical absorption were studied. The gas-sensing properties of the Cs2TeI6-based sensor were investigated at 25 °C using various gases under illumination of a 450-nm laser. Under the blue-light illumination, the sensor exhibited good selectivity toward NO2 gas, with a very low limit of detection of 25 ppb and responsivity of 4.4% toward 1 ppm NO2. The NO2-sensing mechanism was proposed and discussed in term of a surface depletion model. The effects of light intensity, light wavelength, humidity, and long-term duration on NO2-sensing performances were further studied, showing its potential for application into NO2 gas sensors at room temperature. Graphical abstract: Image, graphical abstract